Characteristics of serogroup 20 S.pneumoniae isolates from Brazil - Caierão, Juliana (BMC Infect Dis, 2016)
BACKGROUND: Although serogroup 20 is not part of any conjugate pneumococcal vaccine, its serotype 20A, but not 20B, belongs to the polysaccharide 23-valent formula. Little is known about its clinical, laboratorial and epidemiological characteristics. METHODS: The purpose of this study was to evaluate the bacterial genotypes (by PFGE and MLST), clinical characteristics of patients (from review of medical records) and antimicrobial susceptibility of serogroup 20 isolates which were recovered from patients with invasive pneumococcal disease (IPD) from 2007 to 2012. Subtyping to determine 20A and 20B types was also performed by sequencing the genes of the cps locus. RESULTS: Sixteen isolates were genotyped and were highly related. All pneumococci were resistant to tetracycline and 31 % were non-susceptible to trimethoprim/sulfamethoxazole. Penicillin MIC ranged from 0.004 to 1 μg/mL and non-susceptibility (MIC ≥ 0.12 μg/mL) was observed in 5/16 isolates (31 %). All isolates belonged to subtype 20B. Most patients were male with a median age of 62 years and presented at least one underlying disease (mostly respiratory conditions). All isolates belonged to ST8889 and to a unique PFGE clone. CONCLUSIONS: A high clonal occurrence of serotype 20B pneumococci recovered from patients with IPD in Brazil was observed. As a non-PCV10 serotype, selective pressure may be responsible for this unusual occurrence of serogroup 20. However, temporal variation effect should not be underestimated; therefore it is an issue that warrants continued monitoring.